A Critical Review On Green Talent Management Strategies To Unlock The Organizational Performance (International Journal of Environmental Sciences, 2025)
Green Talent management is one of the fundamental problems public and private sector companies meet. Green Talent Management in an organization is a business strategy that seeks to develop and retain talented and high potential employees. strategic approach of recruiting, developing, and retaining employees with skills, knowledge, and attitudes that align with environmental sustainability goals. This study's research objective is to create a conceptual framework eco-friendly practice into traditional talent management processes to foster a workforce that supports an organization's sustainability objectives. GTM includes practices such as hiring green companies, offering training on sustainability practices, Talent, talent, Sustainable Recruitment and Selection, Green Training and Development, Green Compensation and Benefits program in retaining talent, Sustainable Performance Management, Organizational Commitment towards Talent management strategies, Workplace Environment and Culture, Identify and Differentiate Talented Employees for higher productivity, Sustainable Workforce Planning, Succession Planning, Organizational Performance & Culture, Organizational Employer Branding. This study attempts to address the critical gap in the organization. Thus, this research is essential for academia and manger to develop talent management,increase talent visibility, and develop employees to meet the organization's talent needs. The aim is to enhance the organization's overall sustainability performance while also attracting and retaining talent committed to environmental stewardship.